Impact on granular bed: validation of discrete element modeling results by means of two-dimensional finite element analysis - Marzulli, Valentina; Torres Cisneros, Luis Armando; di Lernia, Annamaria; Windows-Yule, Christopher Robert Kit; Cafaro, Francesco; Pöschel, Thorsten (Granular Matter, 2020)
The study of processes characterized by impulsive nature (i.e. impacts) can be considered of great interest in both physics and engineering disciplines: in the geotechnical field, for instance, their effect on the interaction between soil and structures need to be investigated. The present work aims at the validation, by means of two-dimensional finite element simulations, of a methodology of force calibration which uses results obtained from three-dimensional discrete element analysis for predicting the stress at the base of a granular bed, retained by a movable wall, arising when the system is hit by a projectile. To approach this problem, the low-velocity impact has been modeled as a punctual impulsive force on a granular packing.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Discrete element model; Finite element analysis; Granular material; Impact response; Numerical simulations; Soil–structure interaction